2023
DOI: 10.1021/acs.jpcb.3c02116
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Chloride and Sulfate Pump with Two Different Transport Modes

Abstract: Ion pumps are membrane proteins that actively translocate ions by using energy. All known pumps bind ions in the resting state, and external energy allows ion transport through protein structural changes. The light-driven sodium-ion pump Krokinobacter eikastus rhodopsin 2 (KR2) is an exceptional case in which ion binding follows the energy input. In this study, we report another case of this unusual transport mode. The NTQ rhodopsin from Alteribacter aurantiacus (AaClR) is a natural light-driven chloride pump,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…To date, only three NTQ rhodopsins have been characterized in detail, namely, NM-R3 from Nonlabens marinus ( Flavobacteriia ) (Yoshizawa et al, 2014), FR from Fulvimarina pelagi ( Alphaproteobacteria) (Inoue et al, 2014) and AaClR from Alteribacter aurantiacus ( Bacillaceae ) (Singh et al, 2023). In addition, two identified but incompletely characterized rhodopsins from this group have been reported: PoClR from Parvularcula oceani ( Alphaproteobacteria ) (Inoue et al, 2016) and unnamed protein from Nonlabens sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only three NTQ rhodopsins have been characterized in detail, namely, NM-R3 from Nonlabens marinus ( Flavobacteriia ) (Yoshizawa et al, 2014), FR from Fulvimarina pelagi ( Alphaproteobacteria) (Inoue et al, 2014) and AaClR from Alteribacter aurantiacus ( Bacillaceae ) (Singh et al, 2023). In addition, two identified but incompletely characterized rhodopsins from this group have been reported: PoClR from Parvularcula oceani ( Alphaproteobacteria ) (Inoue et al, 2016) and unnamed protein from Nonlabens sp.…”
Section: Resultsmentioning
confidence: 99%
“…DSM 44513 (GspTR) had absorption peak at 513 nm in 100 mM NaCl and was the most blue-shifted compared to the 24 NTQ rhodopsins available in the Karasuyama et al database (Karasuyama et al, 2018). The absorption peak of GspTR was the closest to that of FR rhodopsin from Fulvimarina pelagi (518 nm in 1660 mM NaCl) (Inoue et al, 2014) and of AaClR from Alteribacter aurantiacus (517 nm in 100 mM NaCl) (Singh et al, 2023), and showed significant distance from NM-R3 rhodopsin from Nonlabens marinus with absorption peak at 533.5 nm (Yoshizawa et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial rhodopsins, also called Type 1 rhodopsins, are mostly present in unicellular microorganisms such as bacteria, archaea, algae, fungi, and protists. Giant viruses have also been reported to possess microbial rhodopsins. Animal rhodopsins, also called Type 2 rhodopsins, are present in only higher animals and work as light-dependent G protein-coupled receptor (GPCR) mediating visual and nonvisual signals or retinal photoisomerase, which catalyzes the isomerization reaction from all- trans -retinal (ATR) to the 11- cis form. ,, In contrast to animal rhodopsins, the functions of microbial rhodopsins are highly diversified. The most abundant types of microbial rhodopsins are light-driven ion pumps that actively transport, e.g., H + , , Na + , Cl – , and SO 4 2– . , In addition, while channelrhodopsins passively transport various ions as light-gated ion channels, , microbial rhodopsins with C-terminal enzyme or ion channel domains have been found; , further, there are many microbial rhodopsins whose functions remain unknown. In 2018, the third class of rhodopsin, heliorhodopsin, was discovered through functional metagenomics . This class is phylogenetically distinct from both microbial and animal rhodopsins and has an inverted molecular orientation in which the N- and C-termini face the cytoplasmic and extracellular sides, respectively.…”
Section: Introductionmentioning
confidence: 99%